2016
DOI: 10.1007/s11270-016-3060-3
|View full text |Cite
|
Sign up to set email alerts
|

Mercury in Marine and Oceanic Waters—a Review

Abstract: Mercury contamination in water has been an issue to the environment and human health. In this article, mercury in marine and oceanic waters has been reviewed. In the aquatic environment, mercury occurs in many forms, which depend on the oxidation-reduction conditions. These forms have been briefly described in this article. Mercury concentrations in marine waters in the different parts of the world have been presented. In the relevant literature, two models describing the fate and behavior of mercury in saltwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 221 publications
(119 citation statements)
references
References 126 publications
3
103
0
5
Order By: Relevance
“…In marine waters, Hg II forms compounds with chlorine (HgCl 3 − and HgCl 4 2− ) to a greater extent than oxides, that are in turn formed in freshwaters (Mason and Fitzgerald ). A lower Hg II methylating activity in marine and estuarine sediments than in freshwater sediments has been attributed to the formation of charged chloride but also sulfide complexes, that undergo a slower methylation processes than other Hg II forms (Gårdfeldt et al ; Jonsson et al ; Gworek et al ).…”
Section: Physico‐chemistry Plays a Pivotal Role In Hgii Methylationmentioning
confidence: 99%
“…In marine waters, Hg II forms compounds with chlorine (HgCl 3 − and HgCl 4 2− ) to a greater extent than oxides, that are in turn formed in freshwaters (Mason and Fitzgerald ). A lower Hg II methylating activity in marine and estuarine sediments than in freshwater sediments has been attributed to the formation of charged chloride but also sulfide complexes, that undergo a slower methylation processes than other Hg II forms (Gårdfeldt et al ; Jonsson et al ; Gworek et al ).…”
Section: Physico‐chemistry Plays a Pivotal Role In Hgii Methylationmentioning
confidence: 99%
“…Artisanal and small-scale gold mining (727 t in 2010, 37% of total anthropogenic emissions) and coal burning (474 t, 24%) were the largest components of anthropogenic emissions in 2010, followed by cement production (173 t), large-scale gold production (97 t), and consumer product waste (96 t). Gworek et al (2016) also showed the similar levels of mercury emission (total emission = 5000-6600 t year −1 ; anthropogenic emission = ~2200 t year −1 ) by citing many papers. Asia contributes almost half of global anthropogenic emissions, accounting 40% of the total emission by East and Southeast Asia, in which China accounts three-quarters (UNEP 2013).…”
Section: Global Mercury Cyclementioning
confidence: 66%
“…Such studies may provide a useful clue as to resolving low-dose mercury issues in the global mercury cycle. Gworek et al (2016) described that the average residence time of mercury in oceanic waters, 20-30 years, is much longer than that in the atmosphere (0.8-2 years), resulting in that the mercury discharged into the ocean is removed from there much more slowly than the mercury emitted into the atmosphere and that an increase in the mercury concentration level in oceanic waters will be very slow and may take hundreds of years. This fact means that the mercury concentration will continue to increase gradually, even if anthropogenic emissions of mercury to the atmosphere stop right now.…”
Section: Outstanding Issuesmentioning
confidence: 99%
“…Mercury is a bioaccumulating and highly toxic heavy metal that causes serious human health problems even at low concentrations, most of all through contamination of drinking water and other natural water resources . This dangerous metal is accumulated in living organisms mainly in its methylated form (CH 3 Hg + ), most prominently in fish tissue along the food chain .…”
Section: Introductionmentioning
confidence: 99%